Solar Energy to Water Desalination: Long-Term Experimental Studies of Solar Still in Poland - Łukasz Mika; Ewelina Radomska (Energies, 2025)
Water scarcity is an escalating global issue which also affects Poland. One of the solutions to this challenge is seawater desalination, particularly using solar stills (SSs). SSs offer a sustainable, low-cost solution for desalination, but their efficiency depends mainly on local solar conditions. Therefore, this study presents long-term experimental results for a single-basin, single-slope SS’s performance in Krakow, Poland, from May to September 2022. The findings show that the SS effectively removed over 98% of total dissolved solids, with a productivity ranging from 1084 to 5014 mL/(m2·day) and water temperatures reaching up to 80.4 °C. These results highlight the feasibility of solar-powered desalination in Poland and contribute valuable data for future optimization.